2018 25th IEEE International Conference on Image Processing (ICIP) 2018
DOI: 10.1109/icip.2018.8451223
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Traumatic Brain Injured Patients: Patient Mood Analysis from Multimodal Video

Abstract: Rehabilitation after traumatic brain injury (TBI) is very critical as it is largely unpredictable depending upon the nature of the injury. Rehabilitation process and recovery time also varies, as it takes months and years, depending upon the assessment of treatment, mental and physical conditions and strategies. Due to non-cooperative behaviour of patients, and increase in negative emotional expressions it is very beneficial to evaluate these expressions in a contactless way, and perform a rehabilitation physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The main aim of this study is to perform facial expression (FE) and mood recognition of TBI patients in order to enhance the social interaction and assist trainers and physiotherapists with the help of robots. First we accumulated a database in three uniform scenarios namely cognitive, physio and social rehabilitation activities, ensuring the reliability of the database as explained in detail in [13], [14]. This database is comprised of 924 videos taken about 11 participants, each being a maximum of 5 second in length, recorded with an Axis RGB and a Logitech RGB camera during multiple sessions at 30fps, resulting in approximately 140,000 captured frames.…”
Section: A Database Development and Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…The main aim of this study is to perform facial expression (FE) and mood recognition of TBI patients in order to enhance the social interaction and assist trainers and physiotherapists with the help of robots. First we accumulated a database in three uniform scenarios namely cognitive, physio and social rehabilitation activities, ensuring the reliability of the database as explained in detail in [13], [14]. This database is comprised of 924 videos taken about 11 participants, each being a maximum of 5 second in length, recorded with an Axis RGB and a Logitech RGB camera during multiple sessions at 30fps, resulting in approximately 140,000 captured frames.…”
Section: A Database Development and Trainingmentioning
confidence: 99%
“…Furthermore, Pepper identifies neutral expressions of TBI patients with only 42% accuracy with sad and neutral expression overlapping, proving that TBI patients' neutral expressions are more likely recognized as sad ones. Experts have annotated the patients' expressions as neutral since their ability to display emotional signals is disturbed due to injury, and during post stroke rehabilitation they exhibit depression and negative emotions more often than positive ones [13], [14]. It is also observed that the Pepper robot failed to identify fatigue expressions due to technical limitations.…”
Section: Pepper Built-in Fer Model Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As these residents are unable to recover from their life-altering impairments fully, the centre provides full-time care to them and aid in organizing and supporting activities of daily living (ADL). The project collaboration aim is to investigate where technological innovation can assist residents and staff members with fulfillment of rehabilitation activities -including enhancing individual self-control and improvement of quality of life [5,6,16].…”
Section: Project Introductionmentioning
confidence: 99%